Electric Properties of Dirac Fermions Captured into 3D Nanoporous Graphene Networks. Issue 46 (11th October 2016) - Tanabe, Yoichi; Ito, Yoshikazu; Sugawara, Katsuaki; Hojo, Daisuke; Koshino, Mikito; Fujita, Takeshi; Aida, Tsutomu; Xu, Xiandong; Huynh, Khuong Kim; Shimotani, Hidekazu; Adschiri, Tadafumi; Takahashi, Takashi; et al.
Abstract : Nanoporous graphene‐ based electric‐double‐layer transistors (EDLTs) are successfully fabricated. Transport measurements of the EDLTs demonstrate that the ambipolar electronic states of massless Dirac fermions with a high carrier mobility are well preserved in 3D nanoporous graphene along with anomalous nonlinear Hall resistance and exceptional transistor on/off ratio. This study may open a new avenue for device applications of graphene.